The Effect of Barrier Fence on Airside Security at Komodo International Airport - Herwanto, Andrian Herwanto; Bagus Harianto, Bambang; Sulkani, Max Genta (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2025)
Airside security at airports is a crucial aspect in supporting the safety and smooth operation of flight activities. One of the key elements in this security system is the perimeter fence. This study aims to analyze the influence of perimeter fence conditions on airside security at Komodo International Airport in Labuan Bajo. Based on field observations, it was found that the airport’s perimeter fencing does not fully comply with the standards set out in PM 167 of 2015 and KP 601 of 2015. Several issues were identified, such as gaps in the fence, uneven height, lack of barbed wire, poor lighting and CCTV coverage, and incomplete inspection pathways.Interviews with Aviation Security (AVSEC) personnel revealed that the suboptimal condition of the perimeter fence is a major challenge in conducting security surveillance and patrols. Questionnaire results from 49 respondents also supported thisfinding, with the majority agreeing that the perimeter fence condition affects the level of airside security. The results of a simple linear regression analysis showed a coefficient of determination (R2) of 0.826 or 82.6%, with a significance value of < 0.05, indicating a statistically significant influence between the condition of the perimeter fence and airside security.Therefore, this study concludes that improvements and regular maintenance of the perimeter fence are essential to strengthen airside security systems and minimize the risks of intrusion, sabotage, or the entry of wild animals into restricted flight operation areas.